Design of 3D Modeling and Interaction on the SEAMOLEC Training Web - Farhan, Muhammad; Fris Okta Falma (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
This report is prepared as part of the Final Project titled